Insights from Syzygium aromaticum Essential Oil: Encapsulation, Characterization, and Antioxidant Activity - Naianny L. O. N. Mergulhão; Laisa C. G. Bulhões; Valdemir C. Silva; Ilza F. B. Duarte; Irinaldo D. Basílio-Júnior; Johnnatan D. Freitas; Adeildo J. Oliveira; Marília O. F. Goulart; Círia V. Barbosa; João X. Araújo-Júnior (MDPI AG, 2024)
Alginate encapsulates loaded with clove essential oil (CEO) were prepared by ionic gelation, with subsequent freeze-drying. The objective of the present work was to develop a product with the ability to protect CEO against its easy volatility and oxidation. The following techniques were used to characterize the formulations: eugenol release, degree of swelling, GC/MS, TGA/DSC, and SEM. The alginate solution (1.0%) containing different concentrations of CEO (LF1: 1.0%; LF2: 0.5%; LF3: 0.1%) was dropped into a 3.0% CaCl2 solution. After lyophilization, the encapsulated samples were wrinkled and rigid, with high encapsulation power (LF3: 76.9% ± 0.5). Three chemical components were identified: eugenol (the major one), caryophyllene, and humulene. The antioxidant power (LF1: DPPH IC50 18.1 µg mL−1) was consistent with the phenol content (LF1: 172.2 mg GAE g−1). The encapsulated ones were thermally stable, as shown by analysis of FTIR peaks, eugenol molecular structure was kept unaltered. The degree of swelling was 19.2% (PBS). The release of eugenol (92.5%) in the PBS solution was faster than in the acidic medium. It was concluded that the low-cost technology used allows the maintenance of the content and characteristics of CEO in the three concentrations tested, offering a basis for further research with essential oil encapsulates.